The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/pce.13935
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate or nitrate imbalance induces stronger molecular responses than combined nutrient deprivation in roots and leaves of chickpea plants

Abstract: The negative effects of phosphate (Pi) and/or nitrate (NO3−) fertilizers on the environment have raised an urgent need to develop crop varieties with higher Pi and/or nitrogen use efficiencies for cultivation in low‐fertility soils. Achieving this goal depends upon research that focuses on the identification of genes involved in plant responses to Pi and/or NO3− starvation. Although plant responses to individual deficiency in either Pi (–Pi/+NO3−) or NO3− (+Pi/–NO3−) have been separately studied, our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 96 publications
(112 reference statements)
4
22
0
Order By: Relevance
“…One possible interpretation of the decline in glucose‐6‐phosphate in both organs is the rapid isomerization of glucose‐6‐phosphate to fructose‐6‐phosphate, especially in the roots of chickpea plants, through glycolysis in response to Pi deficiency. This finding is supported by our previous suggestion (Nasr Esfahani et al., 2021) that under Pi deficiency, glycolysis continues through the induction of the SS/UDP‐glucose pyrophosphorylase pathway and the glycolytic pathway using phosphoenolpyruvate carboxylase/malate dehydrogenase/NAD‐malic enzyme, and thus bypassing the reaction catalyzed by pyruvate kinase despite low adenylate and Pi concentrations in both organs (Figure 7).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…One possible interpretation of the decline in glucose‐6‐phosphate in both organs is the rapid isomerization of glucose‐6‐phosphate to fructose‐6‐phosphate, especially in the roots of chickpea plants, through glycolysis in response to Pi deficiency. This finding is supported by our previous suggestion (Nasr Esfahani et al., 2021) that under Pi deficiency, glycolysis continues through the induction of the SS/UDP‐glucose pyrophosphorylase pathway and the glycolytic pathway using phosphoenolpyruvate carboxylase/malate dehydrogenase/NAD‐malic enzyme, and thus bypassing the reaction catalyzed by pyruvate kinase despite low adenylate and Pi concentrations in both organs (Figure 7).…”
Section: Discussionsupporting
confidence: 88%
“…SK1 and ADT1 ) were downregulated in roots under NO 3 − starvation and/or double nutrient deficiency (Figure 6), whereas the levels of methionine, proline and the aromatic AAs tryptophan, tyrosine and phenylalanine were not declined in the roots by the same nutrient stress treatments (Figures 4 and S8; Table S1). Furthermore, in the roots and leaves of chickpea plants grown under NO 3 − starvation and double nutrient deficiency, increased activities of NAD‐GDH (Figure 5b) in parallel with reduced levels of glutamate (Figures 4 and S8; Table S1) and decreased activities of NADH‐glutamate synthase (GOGAT; Nasr Esfahani et al., 2021) could likely reflect the possibility that N assimilation through NADH‐GOGAT was substituted by deamination of glutamate to NH 4 + and α‐ketoglutarate by NAD‐GDH (Krapp et al., 2011). A similar shift in primary N assimilation in response to changes in N availability has been described in barley ( Hordeum vulgare ; Fataftah et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that plants increased tissue C partitioning from non-structural carbohydrates (NSCs; e.g., soluble sugar and starch) toward secondary metabolites (SMs), such as flavonoids, under P limitation ( Sampedro et al, 2011 ; Liu et al, 2016 ; Shinde et al, 2018 ; Mo et al, 2019 ). Rather than consuming P, secondary metabolism can recycle P from phosphate esters and produce reducing equivalents to scavenge free radicals that are induced by P deficiency ( Malhotra et al, 2018 ; Nasr Esfahani et al, 2021 ). However, according to the growth-differentiation balance hypothesis (GDBH) ( Herms and Mattson, 1992 ), trade-offs of C allocation and partitioning between growth and secondary metabolism exist.…”
Section: Introductionmentioning
confidence: 99%